The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1080/13880209.2021.1942927
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits the pharmacokinetics of simvastatin in rats via regulating the activity of CYP3A4

Abstract: Context: Baicalein and simvastatin possess similar pharmacological activities and indications. The risk of their co-administration was unclear. Objective: The interaction between baicalein and simvastatin was investigated to provide reference and guidance for the clinical application of the combination of these two drugs. Materials and methods: The pharmacokinetics of simvastatin was investigated in Sprague-Dawley rats (n ¼ 6). The rats were pre-treated with 20 mg/kg baicalein for 10 days and then administrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These results suggested that CLZ was easy to be affected by CYP3A4 inhibitors. What’s more, Meng, M. et al found baicalein restrained the enzyme activity of CYP 3A4 in rats liver microsome ( Meng et al, 2021 ). We speculated that baicalein altered pharmacokinetics of CLZ and its metabolites through suppressing CYP 3A4 and P-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that CLZ was easy to be affected by CYP3A4 inhibitors. What’s more, Meng, M. et al found baicalein restrained the enzyme activity of CYP 3A4 in rats liver microsome ( Meng et al, 2021 ). We speculated that baicalein altered pharmacokinetics of CLZ and its metabolites through suppressing CYP 3A4 and P-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…CLZ was mainly metabolized by hepatic cytochrome P450 such as CYP3A4 and CYP2C19 ( Hiratsuka et al, 2007 ), and 3,4-dehydro cilostazol (3,4-CLZ) and 4′-trans-hydroxy cilostazol (4′-CLZ) were two of the main active metabolites. From the past researches, baicalein might be the substrates of CYP3A4 in the vitro metabolism of SD rat liver microsomes ( Zhou et al, 2011 ), and exhibited an inhibitory effect of CYP3A4 in vitro ( Meng et al, 2021 ) . Considering the beneficial effects of baicalein on human health, the potential intake of baicalein for patients who take CLZ in daily life may occur.…”
Section: Introductionmentioning
confidence: 99%
“…Among various isoenzymes of CYP3A, CYP3A4 is one of the most important isoforms that participates in drug metabolism and mediates drug-drug interactions 13 . For example, Li et al investigated the effect of flavonoids on the activity of CYP3A4 and found an inhibitory effect of sophoranone, apigenin, and baicalein 14 , while the interaction of these compounds with other drugs metabolized by CYP3A4 was revealed, in which the inhibition of CYP3A4 has been considered as the main reason for the drug-drug interaction 15 , 16 . Therefore, the inhibition of CYP3A4 by dendrobine implied its potential interaction of CYP3A4-metabolized drugs or chemicals, which should attract attention in the clinical application of dendrobine and Dendrobium .…”
Section: Discussionmentioning
confidence: 99%
“…The AUC of nimodipine increased from 509 to 587 μg/L x h. Both absolute and relative bioavailability increased by 3.4 and 15 value points. Meng et al (2021) also examined baicalein in similar experimental settings in rat models but at a dose of 20 mg/kg [ 118 ]. They determined impaired values of simvastatin (40 mg/kg) and, more precisely, an increase in AUC and C max by almost 220% and 103%, respectively.…”
Section: Flavonoidsmentioning
confidence: 99%